An experimental study on the application of radionuclide imaging in repairing bone defects. (October 2013) - Zhu, Weimin; Wang, Daping; Peng, Liangquan; Zhang, Xiaojun; Ou, Yangkan; Fen, Wenzhe; Lu, Wei; Han, Yun; Zeng, Yanjun
Abstract Objective: In order to study the ability of nano-hydroxyapatite artificial bone in repair of large segmental bone defect and to evaluate the value of radionuclide bone imaging in monitoring the bone's repairing in the bone defect. Methods: The animal model of bone defect was made on the bilateral radius of 24 (New repaired with HA artificial bone) with 12 rabbits in each group. The ability of bone defect repair was evaluated by using radionuclide bone imaging at 2， 4， 8 and 12 weeks postoperatively. Results: The counts of regions of interest (ROI) measure and the target to non-target ratios (T/NT) of the two groups indicate that the experimental group stimulated more bone formation than that of the control group. The differences of the bone reconstruction ability were statistically significant （P ＜ 0.05）. Conclusions: The nano-HA artificial has good bone conduction，it can be used for the treatment of bone defects. Radionuclide imaging may be an effective and first choice method for the early monitoring of the bone's reconstruction.